Visionary Da'wah Strategies of Kiai in Empowering Students as Independent Millennial Farmers - Mutrofin, Mutrofin; Malik, Muhammad Khoirul; Nuha, Mohammad Khadziqun (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2025)
The research in the kiai visionary da'wah strategy is how to take an innovative approach in mobilizing and realizing students to become independent millennial farmers. The lack of studies that examine the integration of da'wah with agricultural economic empowerment among students is one of the gaps in this study. There have been few studies that have explored the role of kiai as an agent of change in addressing the challenges of modern agribusiness today. This research is important for providing an applicable strategic model. The concrete strategies carried out by kiai in realizing millennial farmer students include: first, through the integration of the pesantren curriculum with skills. Second, vocational training programs. Third, partnership programs with external parties. In addition, kiai also implements a learning by doing model so that students are able to implement agricultural science practically. Theoretically, this research contributes to the development of contemporary da'wah theory that integrates spiritual values with agribusiness-based economic empowerment. This study can broaden the understanding that kiai are not only spiritual guides, but also agents of social and economic change. On the other hand, this research also enriches the literature on the visionary da'wah of kiai by emphasizing the aspect of economic independence of students to the needs of the millennial generation in the modern era. Meanwhile, this research can serve as a reference for Islamic boarding schools in designing agriculture-based student empowerment programs aimed at promoting economic independence